Vagus nerve stimulation in Lafora body disease() - Hajnsek, Sanja (Elsevier, 2013)
INTRODUCTION: Lafora body disease (LBD) is a rare autosomal recessive disorder characterized by progression to inexorable dementia and frequent occipital seizures, in addition to myoclonus and generalized tonic–clonic seizures (GTCSs). It belongs to the group of progressive myoclonus epilepsies (PMEs), rare inherited neurodegenerative diseases with great clinical and genetic differences, as well as poor prognosis. Since those patients have a pharmacoresistant disease, an adjunctive treatment option is vagus nerve stimulation (VNS). To date, there are four reported cases of the utility of VNS in PME — in Unverricht–Lundborg disease (ULD), myoclonic epilepsy with ragged-red fibers (MERRF), Gaucher's disease, and in one case that remained unclassified. CASE PRESENTATION: A 19-year-old male patient had progressive myoclonus, GTCSs that often progressed to status epilepticus (SE), progressive cerebellar and extrapyramidal symptomatology, and dementia, and his disease was pharmacoresistant. We confirmed the diagnosis of LBD by genetic testing. After VNS implantation, in the one-year follow-up period, there was a complete reduction of GTCS and SE, significant regression of myoclonus, and moderate regression of cerebellar symptomatology. CONCLUSION: To our knowledge, this is the first reported case of the utility of VNS in LBD. Vagus nerve stimulation therapy may be considered a treatment option for different clinical entities of PME. Further studies with a larger number of patients are needed.